A Kind of New Real-time Scheduling Algorithm for Embedded Linux - Li Yang; Qingyan Zhu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
To solve the insufficiency of real time performance in the present real time scheduling algorithm, a new real time task classification scheduling algorithm is proposed. According to the classification of arrival of real time tasks, this algorithm is divided into periodic tasks and non-periodic tasks, and uses different improved real time scheduling algorithm to schedule different type of real time tasks. Comparing with the present other real time scheduling algorithms, experiments show this algorithm has been largely improved for integrated real time performance. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5480